Profesionalisme, Etika Profesi. Pengalaman Auditor dan Pengaruhnyaterhadap Pertimbangan Tingkat Materialitas pada Kantor Akuntan Publik Padang - D Desmiwerita (SAFE-Network, 2022)
This study aims to determine whether the effect of professionalism, professional ethics and experience of the auditor's consideration of materiality levels either partially or simultaneously. sample in this study is the public accounting firm of auditors in Padang, amounting to a total of 36 respondents from five public accounting firm in Padang. Sampling technique using non probability of sampling. Analysis techniques using multiple linear regression. Based on the analysis found that the auditor professionalism partially significant effect on the level of materiality considerations, while the auditor's professional ethics and partially experience no effect on the level of materiality considerations. The results of simultaneous analysis found that the professionalism, professional ethics and work experience jointly significant effect on the level of materiality considerations